Cardiovascular Changes Among Healthy Elderly - Ikhsan, Muhammad; Boy, Elman (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2020)
Background: World Health Organization (WHO) defines health as a complete physical, mental, and social well-being and not merely the absence of disease or infirmity. Health is one of the important and valuable values among the elderly. Aging is a progress of life in each individual. Unlike pathological conditions, the aging process will occurs in each individual. Elderly tend to experience physical, mental, and spiritual deterioration. The health status of each individual can have an impact on changes in cardiovascular function in the elderly. After each individual reaches the age of 30, heart-lung fitness decreases by 1% for each age, which increases by one year. At the age of 60, heart-lung fitness will decrease until 35%.Objective: To provide an understanding of the cardiovascular changes among healthy elderly.Method: A literature reviewResult: The main effects aging on the cardiovascular system are a changes in vascular structure, a decrease in vascular function, myocytes and atrial pacemaker cells, an increase in cardiac fibrous tissue, a decrease in the function of the ventricular, myocardial contraction, and cardiac output which results in impaired cardiovascular fitness among elderly.Conclusion: The main effects of aging on the cardiovascular system are a decrease in vascular structure, changes in vascular function, a decrease in myocytes and atrial pacemaker cells, an increase in cardiac fibrous tissue, a decrease in ventricular wall function, a decrease in myocardial contraction function, and a decrease in cardiac output function which can ultimately lead to impaired cardiovascular fitness in the elderly.